Proposta de framework para processos de melhoria contínua - Politta, Caroline Cristina (2021)
The market, in general, has become increasingly more competitive and this forces companies to be constantly revising their way of working. The goal is always the same: reduce costs and increase income. A historically proven way of achieving these goals is the use of continuous improvement, one of the pillars of Lean Manufacturing. In this project, a case study was conducted with a company in the region of Curitiba, Paraná. The current process of the company was mapped, and preliminary analysis have shown that even though there are tools for continuous improvement, there is no structured process. Therefore, this project proposes a framework to structure the work on continuous improvement of the department of quality of the company analyzed using quality tools, DMAIC and Design Thinking. Besides that, a form is also proposed to assist in the implementation and generation of data as well as a medium to long term plan for implementation.